Peningkatan Partisipasi Muzakki dalam Pembayaran Zakat: Studi Transformasi Kesadaran Masyarakat - Muhammad Haris; Bayu Indra Laksana; Nur Hasanah; M. Mochtar Mas’od (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2026)
ABSTRACT The increasing participation of muzakki (payers of zakat) in paying zakat is a significant phenomenon in strengthening the economy of the Muslim community and empowering the Muslim community. In the past two years, there has been an increase in the number of muzakki and an increase in the zakat funds collected and distributed, indicating a transformation in religious awareness within society. This study aims to analyze the factors driving this increase in muzakki participation and to examine the transformation in public awareness in the practice of zakat. This study uses a qualitative approach with a case study method, through in-depth interviews, observation, and documentation. The results indicate that the increase in muzakki participation is influenced by religiosity, transparency of zakat institutions, ease of payment technology, and the role of social education. Furthermore, there has been a shift in awareness from normative obligations to collective awareness as an instrument of social empowerment. These findings confirm that zakat is not only a religious obligation but also a mechanism for social transformation in the development of Islamic society.